2020
DOI: 10.1186/s12958-020-00581-4
|View full text |Cite
|
Sign up to set email alerts
|

High serum Antimullerian hormone levels are associated with lower live birth rates in women with polycystic ovarian syndrome undergoing assisted reproductive technology

Abstract: Introduction: Antimullerian hormone (AMH) strongly correlates with ovarian reserve and response to controlled ovarian stimulation. Emerging data suggests that serum AMH level may also predict ART outcomes. However, AMH is characteristically elevated in PCOS women and it is unknown whether it may predict live birth outcomes in this population. Methods: This was a retrospective cohort study of 184 PCOS women (Rotterdam criteria) who underwent their first fresh IVF/ICSI cycle. Women were divided into 3 groups acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 44 publications
7
44
4
Order By: Relevance
“…There have been four studies published that explore the relationship between baseline serum AMH level and pregnancy outcome following IVF/ICSI treatment in PCOS women (15)(16)(17)(18). Our results contrast to these earliest studies (15), in which they enrolled 60 PCOS patients and reported fresh CPR and FR were significantly increased with AMH levels on day 3 of the stimulations cycle.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…There have been four studies published that explore the relationship between baseline serum AMH level and pregnancy outcome following IVF/ICSI treatment in PCOS women (15)(16)(17)(18). Our results contrast to these earliest studies (15), in which they enrolled 60 PCOS patients and reported fresh CPR and FR were significantly increased with AMH levels on day 3 of the stimulations cycle.…”
Section: Discussioncontrasting
confidence: 94%
“…In agreement with previous studies ( 4 , 38 41 ), the number of total oocytes, metaphase II oocytes, and >14 mm follicles were statistically different in groups in our study, verifying the positive predictive value of baseline AMH levels on the ovarian response to stimulation regimen. The total consumption of gonadotrophins progressively decreased from low to high baseline in the AMH group, which is consistent with previous data indicating that baseline AMH levels positively predict ovarian responsiveness to gonadotrophin in PCOS ( 15 , 17 , 18 , 42 ). The estradiol (E2) level on the day of hCG administration was significantly positively correlated with serum AMH levels in this cohort.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations